A comparison of nutrition knowledge, attitudes and dairy consumption of school children according to age and gender - Irena Colić Barić (Mljekarstvo)
Besides traditional nutrients, milk and dairy products contain some health promoting components. The aim of this study was to detect the frequency and preferences among dairy products in school children according to age and gender. The subjects were 234 healthy children at age 10-11 years and 14-15 years from two primary schools in Zagreb. Number of participants was well balanced according to age and gender. Dietary data were collected using specially designed food frequency questionnaire (FFQ). By additional questionnaire some anthropometric parameters as well as food preferences, attitudes and nutrition knowledge on milk and dairy products were collected. According to the results the intake of milk is significantly different (p< 0.05) to gender but not to age. 91 % children consume milk, 2.3 cups/day in average. Soft drinks, fruit juices, beverages and similar drinks are consumed more often than milk. Pudding and ice cream had the highest frequency among dairy products consumed. Milk and dairy frequency intake according to age and gender are still not significantly different. Children mostly consume fresh milk (68.7%). Girls at age 14-15 years consume light milk ( ≤1.6 % fat) more than younger children and boys at the same age. 86 % of children is well informed about nutritional facts linked to milk and dairy products and they are mostly educate by parents. Among anthropometric parameters a statistically significant difference (p<0.05) was observed in height with regard to gender, only among older children, and for both height and, weight and body mass indeks (BMI) with regard to age.